The effect of strategic orientation, internal environmental management, and environmental performance on green supply chain management - Bilaludin, Bilaludin (Universitas Ahmad Dahlan, 2024)
Purpose-Basically, the process of fulfilling human activities will certainly have impacts, including environmental pollution. Environmental pollution carried out by irresponsible parties will cause environmental damage. Therefore, every business actor is expected to consider production activities in a more mature and planned manner, which in turn can have a positive economic, environmental and social impact. This study aims to analyze the factors that influence the implementation of green supply chain management, namely strategic orientation, internal environmental management, and environmental performance. Design/Methodology/Approach-Using the purposive sampling technique, 110 micro, small, and medium-sized businesses in Yogyakarta, Indonesia's batik industry made up the study's sample. Questionnaires were distributed to respondents in order to collect data. The Likert scale is used to measure the respondents' responses. To ensure data validity, reliability, and hypothesis testing, Smart PLS analytic techniques were used. Findings-The findings show that green supply chain management benefited from strategic direction, internal environmental management, and environmental performance. These findings show that, according to the three influencing criteria, micro, small, and medium-sized businesses in Yogyakarta, Indonesia's batik industry have successfully incorporated green supply chain management into their daily operations. Research limitations/implications-This study is limited to micro, small, and medium-sized businesses in Yogyakarta, Indonesia's batik industry. The application of green supply chain management to Indonesia's micro, small, and medium-sized business sector as a whole cannot be extrapolated from the study's findings. Originality/value-Previous research has not used objects like those in this study. Previous research used micro, small and medium enterprises with different sectors in other regions of Indonesia.